Educação especial & educação inclusiva: a emergência da docência inclusiva na escola contemporânea - Hermes, Simoni Timm (2017)
How does the articulation between Special Education and Inclusive Education function in the modes of subjectivation of teachers in the contemporary school? This research problem has derived from concerns about the way that teachers have constituted the teaching action in the place of truth of school inclusion, particularly after the National Policy for Special Education under the Inclusive Education Perspective was enacted. This Doctoral Thesis in Education aims to understand the articulation between Special Education and Inclusive Education in the contemporary school in order to problematize its effects on the modes of subjectivation of teachers. Specifically, the Thesis attempts to map the articulation between Special Education and Inclusive Education intended to the production of teachers in the contemporary school; to analyze the process of molding teachers working in Special Education and regular classrooms; and to problematize the historical condition of the articulation between Special Education and Inclusive Education in the production of teachers in the contemporary school. From Michel Foucault‟s philosophical perspective and contributions from the Foucauldian Studies in Education, subjectivation has been selected as a central analytical tool in the theoretical-methodological matrix of this research, while the notions of governmentality, noopolitics, social subjection and machinic servitude have been taken as tangential aids in this problematization. The materiality of the research practice has been organized by means of the contexts of emergence and proveniences, through a genealogical inspiration. In the context of emergence, legal documents or official publications related to educational goals, teacher education and school practices in our country nowadays have been problematized. In the context of proveniences, school documents of a State School situated in the city of Santa Maria, in the state of Rio Grande do Sul, in Brazil, have been analyzed. This school has been regarded as a reference in school inclusion of the Special Education target group, and mentioned in the materiality of the school practices; it is a pioneer in the pedagogical work with this target group in Santa Maria and Rio Grande do Sul. Furthermore, 12 Special Education teachers that worked and still work in this State School, and four teachers of regular classrooms were interviewed. This theoretical-methodological endeavor has evidenced that, in the articulation between Special Education and Inclusive Education, inclusive teachers have emerged as this group of Special Education and regular classroom teachers that act in favor of school inclusion. Historically, the axes of moralization, psychologization and democratization, which are present in the ways of becoming a teacher in the school practices, have been conditions of possibility for inclusive teaching. Thus, a process of molding of those teachers has been produced by inclusive teaching through the inclusive self, the articulation, the pedagogical expertise and innovation in the contemporary school.